Effect of short-term intake of four sweeteners on feed intake, solution consumption and neurotransmitters release on mice - Ren, Jing-Nan (J Food Sci Technol, 2020)
This study focused on the effect of short-term intake of sweeteners on feed intake, solution consumption and neurotransmitters release on mice. The results showed that the free drinking of 10 mM sucralose solution, 100 mM maltose solution, 3 mM saccharin solution and 3 g/L stevioside solution for 32 days will not affect the normal development of the body weight and feed intake of the mice. The consumption of maltose solution was significantly higher than that of the other sweeteners. The leptin and insulin levels increased significantly after the short-term intake of these four sweeteners. The dopamine (DA) content in the whole brain of the mice increased significantly only in the maltose group. These results indicate that the short-term intake of the preferred concentrations of maltose, stevioside, sucralose and saccharin will not affect the body weight and feed intake of the mice. Mice prefer maltose solution to other sweeteners solutions. The 100 mM maltose solution and 3 mM saccharin solution could result in the oxidative stress on mice after 32 days’ short-term intake. Compared with other sweeteners, only sugars that could be broken down into small molecules of glucose might have a positive effect on dopamine levels.